Peran Ekonomi Kreatif dalam Pemberdayaan Ekonomi Masyarakat di Desa Wisata Rotan Trangsan, Gatak, Kabupaten Sukoharjo - Ika Swasti Putri; Dwi Wahyuningsih (Global Financial Accounting Journal, 2021)
The current pandemic situation shows that the creative economy is a solution for economic progress because it can create jobs, increase export revenues, as well as promote the potential of various regions so that it can attract investors. Trangsan Village, Gatak District, Sukoharjo Regency is an area known for its rattan-based handicrafts. This craft can be used as raw material for various household furniture such as tables, chairs, wall hangings, and so on. The pandemic situation has made Trangsan Village rattan craftsmen innovate in order to continue to gain profits. Rattan craftsmen in Trangsan Village became the object of this study so that this research was qualitative and was conducted in January 2020. Interviews and observations were carried out as a method for researchers to obtain data using a qualitative approach. Based on the results of the research, it was found that the role of the creative economy for the creative industry in Trangsan Village after Covid was to be able to empower the community, spur people's creativity to maximize resources and increase foreign exchange for the local government, especially Sukoharjo Regency in the midst of a pandemic.